3-D printed 1.1 THz waveguides - Otter,WJ; Ridler,NM; Yasukochi,H; Soeda,K; Konishi,K; Yumoto,J; Kuwata-Gonokami,M; Lucyszyn,S (Electronics Letters, 2017)
Abstract:For the first time, 3D printed metal-pipe rectangular waveguides (MPRWGs) have been demonstrated in the WM-380 (500-750 GHz) and WM-250 (750 GHz-1.1 THz) waveguide bands. The ultra-high spatial resolution offered by the new RECILS additive manufacturing technology enables the precision fabrication of these prototype MPRWGs at such high frequencies. This enabling technology avoids the need for access to expensive microfabrication resources and, thus, opens up the terahertz spectrum to the low-cost manufacture of passive components.